L'engendrement des choses: des hommes, des femmes et des techniques - Chabaud-Rychter, Danielle; Gardey, Delphine (EAC, 2002)
"Le monde contemporain est marqué par une amplification des biens et des choses, des techniques et des artefacts ; toutes choses nous semblant à la fois ordinaires, évidentes et neutres. Cette modernité est rarement interrogée du point de vue des hommes et des femmes qui la vivent. Pourquoi en effet prêter des intentions aux choses? Elles participent de nos vies, pourvoient à nos besoins, nous soulagent de bien des tâches. Remettre en question la neutralité des techniques est pourtant une bonne façon de s'interroger sur les rapports sociaux de sexes, en se demandant pourquoi les femmes sont durablement exclues de certains domaines techniques ; quel pouvoir confère la maîtrise des techniques ; quel est l'enjeu politique et symbolique de cette maîtrise ; et, au bout du compte, comment les techniques contribuent à ordonner le social, et en particulier les relations sexuées."
Section: 328 p. : ill. ; 22 cm.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Climate change vulnerability, impacts, and adaptation: Why does gender matter? - Denton, Fatma (Gender & Development, 2002)
Gender-related inequalities are pervasive in the developing world. Although women account for almost 80 per cent of the agricultural sector in Africa, they remain vulnerable and poor. Seventy per cent of the 1.3 billion people in the developing world living below the threshold of poverty are women. It is important that the consequences of climate change should not lead already marginalised sections of communities into further deprivation. But key development issues have been at best sidetracked, and at worst blatantly omitted, from policy debates on climate change. The threats posed by global warming have failed to impress on policy-makers the importance of placing women at the heart of their vision of sustainable development. This article argues that if climate change policy is about ensuring a sustainable future by combining development and environment issues, it must take into account the interests of all stakeholders. The Global Environment Facility and the Clean Development Mechanism of the Kyoto Protocol can play a role in ensuring sustainable development, provided they are implemented in a way that does not disadvantage women and the poor.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; changements climatiques; discipline; environnement; projet charge mentale; périodes historiques; santé; science politique; science politique et droit; thématiques

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis